Activating the Library and Making a Reading Corner SD Negeri 010 Sungai Simpang Dua Village as a Form of Concern for Children's Reading Literacy - Dede Permana; Airo sejuki El Fadhli; Rafita Rafita; Wan Sabina Putri; Monica Andella; Refni Yunita; Aliyah Aziz; Muhammad Alvin Febrian; Yoza Aditya Pramudita; Monika Uli Siregar; Yeni Pramita (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Man needs education in life with the aim of shaping dispositions and good character. In this case, the basic education that must be built is reading literacy in early childhood, the knowledge of knowledge can be obtained and read a lot. Purpose of the activity this community service is to reactivate a library that has not been in a long time once visited by students of SDN 010 Desa Sungai Simpang Dua  and made a reading corner which is interesting and convenient to revive the reading interest of students of SDN 010 Desa Sungai Simpang Dua. The target of the service is SDN 010 Desa Sungai Simpang Dua, sub-district Kampar left. The activity is carried out for approximately 4 days starting on July 13, 2022, 23-26 July 2022, the stages of activities are preparation, implementation, and documentation. Preparation begins by conducting a site survey and obtaining permission to carry out activities in elementary schools. The implementation is carried out by cleaning the entire library room and create a reading corner by utilizing the creativity of processed origami paper and other papers. Documentation is carried out by allowing the students to feel the atmosphere again a long-closed library while directing students to read books in a reading corner and done documentation with the students present and some teachers.